Study guide to accompany the economy today - Wilson, Ziegler (McGraw-Hill Companies, Inc, 2017)
This Study Guide is an important part of the complete and fully integraled textbook package called The Economy Today. Students who use this Study Guide on a continuous basis should be able to remember what they have read in their textbook and heard in your lecture. It should enabie them to apply the principles they leam to examinations and, more importantly, should help them recognize the same principles ạt work in their daily experiences. Each section of each chapter has a particular objective, which is described the following paragraphs.